Thigh Abscess Caused by Yersinia enterocolitica in an Immunocompetent Host - Purva Gumaste; V. Subbarao Boppana; Amarinder Singh Garcha; Donald Blair (Case Reports in Medicine, 2012)
Yersinia enterocolitica is primarily a gastrointestinal tract pathogen known to cause gastroenteritis, although it may produce extra-intestinal infections like sepsis and its sequelae. However, primary cutaneous infections are extremely rare. We present a case of Y. enterocolitica thigh abscess in an immunocompetent adult. The portal of entry is unclear in this case. He did many outdoor activities that involved skin injuries and exposure to soil and contaminated water. Hence, direct inoculation as a result of exposure to contaminated water is postulated in the absence of evidence for a gastrointestinal route of infection.